Clean Energy and Fuel (Hydrogen) Storage - Srinivasan, Sesha (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Clean energy and fuel storage are often required for both stationary and automotive applications. Some of these clean energy and fuel storage technologies currently under extensive research and development include hydrogen storage, direct electric storage, mechanical energy storage, solar-thermal energy storage, electrochemical (batteries and supercapacitors), and thermochemical storage. The gravimetric and volumetric storage capacity, energy storage density, power output, operating temperature and pressure, cycle life, recyclability, and cost of clean energy or fuel storage are some of the factors that govern efficient energy and fuel storage technologies for potential deployment in energy harvesting (solar and wind farms) stations and onboard vehicular transportation. This Special Issue thus serves the need for promoting exploratory research and development on clean energy and fuel storage technologies while addressing their challenges to practical and sustainable infrastructures.